Utilizing Plastic Waste into Paving Blocks - Nanda, Maghfira Mei; Nugraha, Parma Adi; Budi, Alif Setia; Prayoga, Arjun Bangkit; Anggita, Faqih Sabili; Irrawan, Mahda Salsabela; Wijayanti, Evi; Nurhidayah, Nunik; Purwaningsih, Mila; Anjarni, Riski Dwi Ayu; et al. (Proceedings Series on Social Sciences & Humanities, 2025)
Gambuhan Village, located in Pulosari District, Pemalang Regency, remains a major concern due to its geographical location and environmental issues, resulting in the accumulation of waste. This situation has the potential to cause pollution if not managed properly. The high use of plastic in people’s daily activities has led to an increase in plastic waste, which takes a very long time to decompose naturally. One innovative effort to reduce environmental pollution is to utilize plastic waste as a mixed material in the manufacture of paving blocks. This research aims to implement waste management in Gambuhan Village, as well as educate and demonstrate to residents to be more aware, care about, and participate in waste management. This research also explores the process of processing plastic waste into paving blocks and tests the quality of the resulting product, starting from the process of selecting and collecting certain plastic waste, cleaning, and mixing with additional materials such as sand and cement. It also uses a mixture of EM4, goat urine, molasses, and natural kitchen ingredients.